Design, Synthesis, and Optoelectronic Characterization of a Novel Cu(II) Complex-Based Photodiode with Prof. Dr. Yakuphanoglu's Advanced Fytronix Solar Simulator Characterization Techniques - Dere, Aysegul; Erdener, Digdem; Yalcin, Mesut; Ozdemir, Namik; Dayan, Osman; Mansour, Shehab; Yakuphanoğlu, Fahrettin (Pergamon-Elsevier Science Ltd, 2026)
In this study, a Cu(II) complex, [CuLCl2], containing pyridine-2,6-dicarboxamide (L) and two chloro ligands was synthesized from the reaction of CuCl2 & sdot;.2H2O with pyridine-2,6-dicarboxamide in methanol and characterized for optoelectronic applications. X-ray crystallography confirmed the monoclinic structure of the complex and the presence of a square pyramidal geometry around the Cu(II) ion. Further characterization was performed using FT-IR spectroscopy, mass spectrometry, and electrochemical analysis. Additionally, the photonic device was fabricated by incorporating the Cu(II) complex as a layer on a p-type silicon substrate. The electrical and optical properties of the device were investigated at different illumination intensities. The current-voltage (I-V) characteristics indicate that the photodiode generates significant photocurrent under illumination. The device exhibited a stable and rapid photoresponse. The responsivity (R) and detectability (D*) values of the photodiode were measured as 2.9 mA/W and 1.95 x 1013 Jones, respectively, at an illumination intensity of 80 mW/cm2. Time-dependent photo-response and detection analyses demonstrated the stability of the diode under light on-off cycles.
Keywords: Cu(II) complex; Pyridine-2; 6-dicarboxamide; Photodiode; Optoelectronic applications; Responsivity; Fytronix Solar Simulator